HALVING POVERTY IN INDONESIA - Auwalin, Ilmiawan (Journal of Indonesian Economy and Business, 2009)
This study extends the literature on relationship between economic growth, income inequalities, and poverty reduction. We discuss poverty reduction, using the case ofIndonesia, as one of the Millennium Development Goals declared by the United Nations General Assembly in September 2000. Using provincial level data of Indonesia from 1993 to 2000, we examine the required conditions in order to halve the poverty in Indonesia by2015. The result of analysis shows that Indonesia would need to achieve constantly 8 percent economic growth in order to halve the poverty rate by 2015. In addition, analysis on the relationship of income inequalities and poverty reduction in Indonesia also shows that improvement on income distribution will have fairly significant impact in poverty reduction.Keywords: economic growth, income inequalities, and poverty reduction